A Matched Cohort Study of Standard Chemo-Radiotherapy versus Radiotherapy Alone in Elderly Nasopharyngeal Carcinoma Patients - Zeng, Qi (PLoS One, 2015)
The impact of standard chemo-radiotherapy (CRT) as preferred therapy for elderly patients (age≥60 years) with nasopharyngeal carcinoma (NPC) remains unclear. Therefore, a strict matched cohort study was conducted to compare the survival and treatment toxicity of standard chemo-radiotherapy in the elderly NPC patients with those of radiotherapy (RT) alone. From 1998 to 2003, total 498 newly diagnosed elderly non-metastatic NPC patients were abstracted and classified into two groups by the treatments they received. For each patient in the CRT group, a matched pair in RT group was identified by matching for gender, age, histological type, T and N classifications, RT dose to primary tumor and neck nodes, and days of radiotherapy. Treatment tolerability and toxicity were clarified, and treatment outcomes were calculated and compared between the two groups. Two groups were well balanced in clinical characteristics because of the strict matching conditions. Totally 87 pairs can be assessed according to the criteria. The 5-year OS, CSS, FFS, and LR-FFS for CRT and RT groups were 62% versus 40% (P=0.013), 67% versus 47% (P=0.018), 65% versus 53% (log-rank: P=0.064, Breslow: P=0.048), and 88% versus 72%, (P=0.019), respectively. There was no significant difference in 5-year D-FFS between the two groups (75% vs. 73%, P=0.456). The CRT group experienced significantly more Grade ≥3 acute mucositis (46.0% vs. 28.7%, P= 0.019). We concluded that standard chemo-radiotherapy can achieve a reasonable local and regional control in elderly NPC patients with acceptable and reversible acute toxicity. However, distant metastasis remains the dominant failure pattern. When the elderly NPC patients are in good performance status following a complete evaluation of overall functional status and comorbidity conditions, standard chemo-radiotherapy is worthy of recommendation.